Evaluation of FAIR in a residential treatment facility through character education lenses - Helfrich, Christine Mary, author; Palermo, Francisco, advisor; Le, Thao, advisor; Banning, James H., committee member (Colorado State University. Libraries, 2010)
The increasing ethnic, cultural, language, and class diversity in the U.S. calls for a proactive approach in helping young people develop into socially competent adults. FAIR: Fairness for All Individuals through Respect is an experiential multicultural education program that addresses fairness in social interactions. The purpose of this study was to evaluate the effectiveness of FAIR for at-risk youth in treatment facilities in Northern Colorado. In order to identify change in participants' level of respect, responsibility, and fairness, two measures, the Role Model Inventory and the Character Development Survey, were administered before and after FAIR. Results revealed that individuals who participated in FAIR curriculum versus individuals who were wait-listed did not differ significantly in their levels of respect, responsibility, and fairness. Although results were not statistically significant, the study provides a valuable framework for conducting future research in the field of character education with at-risk youth.
Department Head: Karen Caplovitz Barrett.